Phytochemical and Cytotoxic Aspects of Amaryllidaceae Alkaloids in Galanthus Species: A Review - Borislav Georgiev; Boriana Sidjimova; Strahil Berkov (Plants)
The genus Galanthus (Amaryllidaceae) currently contains 25 plant species naturally occurring in Europe and the Middle East region. These perennial bulbous plants possess well-known medicinal and ornamental qualities. Alkaloid diversity is their most distinctive phytochemical feature. A total of 127 compounds (≈20% of all known Amaryllidaceae alkaloids) grouped in 16 structural types have been previously found in Galanthus extracts. Some structural types like galanthindole, graciline and plicamine were first discovered in Galanthus plants. Nine Galanthus species, however, remain unstudied regarding their alkaloid patterns. Intraspecific variability has only been studied in G. nivalis and G. elwesii. Amaryllidaceae alkaloids are molecules with anticholinesterase, antibacterial, antifungal, antiviral and anticancer properties. Galanthamine, isolated for the first time from Galanthus woronowii Losinsk., stands out as an acetylcholinesterase inhibitor approved for medical use by the FDA for the treatment of symptoms of Alzheimer’s disease. Lycorine, narciclasine and pancratistatin are noteworthy cytotoxic and antitumor alkaloids. Structural types like galanthamine, homolycorine and haemanthamine are fairly well studied in anticancer research, but little to no information is available on galanthindole, graciline and other types. This review aims to present an update on the alkaloid diversity of Galanthus spp. and highlight the need for further research on the antitumor potential of these molecules.